From C0 to C6: Expanding Bloom’s Taxonomy to Diagnose Passive Learning in AI-Mediated Classrooms - Masduki Asbari (Yayasan Aya Sophia Indonesia, 2025)
The rapid integration of generative artificial intelligence (AI) into educational environments has reshaped the way learners access and engage with knowledge. While AI offers unprecedented efficiency and convenience, it has simultaneously created conditions that foster passive learning behaviors, particularly copy-pasting without cognitive involvement. This phenomenon contributes to a degradation of higher-order thinking, popularly termed “brain rot.” This article introduces the concept of Zero Order Thinking State (ZOTS) as a new pre-cognitive category—designated as C0—that precedes the lowest level of Bloom’s Taxonomy. ZOTS represents a non-cognitive state in which learners exhibit no mental activation, processing, or interpretation of information. Through a reflective qualitative approach grounded in conceptual analysis, this study synthesizes contemporary literature on AI-assisted learning, cognitive psychology, and digital distraction to formalize the C0–C6 pedagogical matrix. Findings indicate that ZOTS is not merely a lower level of cognition but a null cognitive condition that requires urgent pedagogical and policy intervention. The expanded taxonomy proposed in this study offers educators a strategic framework to diagnose and mitigate ZOTS while promoting more ethical, reflective, and epistemically aware uses of AI. The article contributes both theoretical insights and practical strategies essential for designing learning environments that preserve human cognition in an era of technological acceleration.